Evaluation of maize and forage sorghum silage using Boran steers - Mitaru, B.N. (1978)
Digestion and feeding trails were conducted to evaluate maize and forage sorghum silages in terms of chemical composition, digestibility and animal performance. A digestion trail, using six steers was conducted and treatments were: (1) maize silage; (2) forage sorghum silage. Feed intake and water intake were measured. A feeding trails using 27 forage sorghum silage. Twelve steers were allocated to treatment one while the rest were allocated to treatment two. Feed intake and weight gains were measured. Feed, weigh back, faeces and urine samples were chemically analysed using methods by AOAC (1975) and Van Soest (1963). Feed intake and digestibility coefficients data were subjected to analysis of variance. Student ‘t’ test was used to compare the means of feed chemical composition and animal performance. Dry matter content (30.65%; 34.75%), Crude protein (7.16%; 6.99%), Ether extract (4.47%; 3.86%), ASH (9.78; 9.23%) and gross energy in Kcal/g (DM) (4.07; 4.16) were not different (P<. 05) in maize and forage sorghum silages respectively. The fibrous components were lower (P<. 01) in maize silage than in forage sorghum silage, i.e. Crude fiber (29.25%; 38.05%), Cell wall content (54.49%; 68.99%), Acid detergent fiber (37.52%; 48.65%) and Acid detergent lignin (3.88; 5.95%) respectively. Silage juice for pH determination was squeezed out using cheese cloth. The pH in Maize and forage sorghum silages were 4.04 and 4.21 respectively. Maize silage was higher (p<. 05) in digestibilities of dry matter and energy than forage sorghum silage. Digestibilities of crude fiber, cell wall content and acid detergent fiber were higher (P<0.01) in maize silage than in forage sorghum silage. The lower digestibility of forage sorghum silage may have been due to its higher lignin content. Crude protein digestibility for maize (34.17% and forage sorghum silage (28.17%) were not different (P<0.05). Whole grain kernels were isolated from the silages as fed and also from faeces samples. Maize silage grain kernels were more digestible than forage sorghum silage whole grain kernels. In the digestion trial, forage sorghum dry matter intake (69.76 g/w0.75) was higher (P<0.05) than for maize silage (60.20g/w0.75). The difference in dry matter intake may have been due to difference in dry matter content of the silages. In the feeding trail the dry matter intake for maize silage (79.37 g/w0.75) and for forage sorghum silage (82.17 g/w0.75) were not different (p<.05). The average dry matter intake was higher in the feeding trial than in the digestion trail. The may have been due to group feeding effect in the feeding trail. Confinement in the digestion trail may also have caused stress, which may have lowered the feed intake. Steers on forage sorghum silage had higher (P<0.05) weight gains than those on maize silage. The steers used in the trial were brought from range areas and they were in poor condition. Their poor condition prior to the trial period and inexposure to silage feeding may have contributed to their performance. On average maize and forage sorghum silage maintained the weight of the steers.